Triportheus albus Cope, 1872 in the Blackwater, Clearwater, and Whitewater of the Amazon: A Case of Phenotypic Plasticity? - Araújo, José D. A.; Ghelfi, Andrea; Val, Adalberto L. (Frontiers in Genetics, 2017)
The Amazon basin includes thousands of bodies of water, that are sorted according to their color in three types: blackwater, clearwater and whitewater, which significantly differ in terms of their physicochemical parameters. More than 3,000 species of fish live in the rivers of the Amazon, among them, the sardine, Triportheus albus, which is one of the few species that inhabit all three types of water. The purpose of our study was to analyze if the gene expression of T. albus is determined by the different types of water, that is, if the species presents phenotypic plasticity to live in blackwater, clearwater and whitewater. Gills of T. albus were collected at well-characterized sites for each type of water. Nine cDNA libraries were constructed, three biological replicates of each condition and the RNA was sequenced (RNA-Seq) on the MiSeq® Platform (Illumina®). A total of 51.6 million of paired-end reads, and 285,456 transcripts were assembled. Considering the FDR ≤ 0.05 and fold change ≥ 2, 13,754 differentially expressed genes were detected in the three water types. Two mechanisms related to homeostasis were detected in T. albus that live in blackwater, when compared to the ones in clearwater and whitewater. The acidic blackwater is a challenging environment for many types of aquatic organisms. The first mechanism is related to the decrease in cellular permeability, highlighting the genes coding for claudin proteins, actn4, itgb3b, DSP, Gap junction protein, and Ca2+-ATPase. The second with ionic and acid-base regulation (rhcg1, slc9a6a (NHE), ATP6V0A2, Na+/K+-ATPase, slc26a4 (pedrin) and slc4a4b). We suggest T. albus is a good species of fish for future studies involving the ionic and acid-base regulation of Amazonian species. We also concluded that, T. albus, shows well defined phenotypic plasticity for each water type in the Amazon basin.